Risiko Kesehatan dalam Mempertahankan Ekonomi Keluarga pada Petani Penyemprot Pestisida di Desa Larangan Kabupaten Brebes - Ibrahim, Ilyas (FORIKES, 2022)
Intensive use of toxic chemicals can have a negative impact on environmental ecosystems and public health. Farmers as pesticide sprayers on agriculture have the risk of being affected by pesticides. The problem of the family's economic needs makes farmers survive the health risks caused by these toxic materials. Long-term exposure to chemical pesticides can have a negative impact on human health, especially systemic diseases. Difficult economic pressures related to family income, family needs and family health cause farmers to succumb to health risks. This study aims to describe the health risks in maintaining the family economy of pesticide spraying farmers in Brebes Regency. Indonesia. This study used a qualitative method with case studies and interviews with informants (heads of families). Respondents were interviewed to find out the health and economic conditions of their families. The collected data was then compiled to describe the health and economic conditions experienced by the head of the household. Respondents were interviewed that the economic pressures were so severe that they ignored the health risks they faced. It was concluded that the activity of spraying pesticides in agriculture was carried out routinely as farmer workers to meet the economic needs of the family. Health risks such as pesticide poisoning that cause health problems, the heat of the sun, rain and fatigue are ignored because there is no other choice to maintain the family's economy.Keywords: health risk; family economy; pesticide spraying farmerABSTRAK Penggunaan bahan kimia beracun secara intensif dapat berdampak buruk pada ekosistem lingkungan dan kesehatan masyarakat. Petani sebagai penyemprot pestisida pada pertanian memiliki risiko terkena dampak pestisida. Masalah kebutuhan ekonomi keluarga membuat petani bertahan dari risiko kesehatan yang ditimbulkan dari bahan beracun tersebut. Paparan pestisida kimia dalam jangka panjang dapat berdampak buruk bagi kesehatan manusia, terutama penyakit sistemik. Tekanan ekonomi yang sulit terkait pendapatan keluarga, kebutuhan keluarga dan kesehatan keluarga menyebabkan petani menyerah pada risiko kesehatan. Penelitian ini bertujuan untuk mendeskripsikan risiko kesehatan dalam mempertahankan ekonomi keluarga petani penyemprot pestisida di Kabupaten Brebes. Indonesia. Penelitian ini menggunakan metode kualitatif dengan studi kasus dan wawancara dengan informan (kepala keluarga). Responden diwawancarai untuk mengetahui kondisi kesehatan dan ekonomi keluarganya. Data yang terkumpul kemudian disusun untuk menggambarkan kondisi kesehatan dan ekonomi yang dialami oleh kepala keluarga. Responden diwawancarai bahwa tekanan ekonomi begitu sulit sehingga mereka mengabaikan risiko kesehatan yang mereka hadapi. Disimpulkan bahwa aktivitas penyemprotan pestisida di pertanian dilakukan secara rutin sebagai pekerja petani untuk memenuhi kebutuhan ekonomi keluarga. Risiko kesehtana seperti keracunan pestisida yang menimbulkan gangguan kesehatan tubuh, panasnya matahari, kehujanan dan kelelahan diabaikan karena tidak ada pilihan lain untuk mempertahankan ekonomi keluarga.Kata kunci: risiko kesehatan; ekonomi keluarga; petani penyemprot pestisida